narendran1990 wrote:
msk0657: Couldn't quite understand the concept in point no:3. General form of the equation is ax+by+c=0.
If y=-x, then substituting the same is the equation y=mx+b, would give -1=m+b, m=-1-b. But then without knowing value of 'b', 'm' cannot be determined. Can you explain.?
Hi Narendran,
1. General form.The general form of the equation of a straight line is ax+by+c = 0.
Where a,b and c are arbitrary constants. This form includes all other forms as special cases. For an equation in this form the slope is -a/b and the y intercept is -c/b.
2. Point-intercept form.
y = mx+b.
Where: m is the slope of the line; b is the y-intercept of the line; x is the independent variable of the function y .
We know the standard equation form is ax+by+c=0 , which you mentioned correctly. We can write like this y = (-a/b)x + (-c/a) , here y intercept is (-c/a) and slope is (-a/b).
We are given only y+x = 0 and let's write this one in the above converted form i.e. => y = (-1)x + 0 , we are not given any b value i.e. y-intercept value and if we compare equation with the standard one then we can see slope is -1 and it is -ve value.
Hope this is clear...Please let me know if this is not clear.